Gardening and Garden Therapy as a Resource for Human Psychological Well-Being - Polina O. Andzaurova; Sofya K. Nartova-Bochaver (Peoples' Friendship University of Russia (RUDN University), 2023)
Gardening, as one of the most popular active types of interaction with the world of flora, is used by people to meet various needs (e.g., intellectual, social and some others). However, its restorative potential for the psyche of a person living in the digital era and the urban environment remains underestimated. The authors examine the main effects of gardening activities and therapy on the physical and psychological state of a person, as well as its potential in the context of strengthening social ties and social engagement. There are also positive effects of gardening on the psychological state of children. The research potential of gardening activities as a way to reduce the psychological distress resulting from social isolation and sedentary lifestyles during the COVID-19 pandemic is highlight. In addition, an analysis is made of the possible mechanisms of the beneficial effect of gardening on people's mental health both within the framework of specific theories, including the stress reduction theory, the attention restoration theory, the theory of phyto-resonance, and in the context of individual modern studies. The literature review was carried out based on the analysis of studies in different countries of the world (Australia, Great Britain, Iran, Italy, Oman, Romania, Singapore, USA, Taiwan and Sweden). The limitations of some of the studies under consideration are presented, mostly concerning the purity of their design; study vectors for further research and practical application are also outlined.